2011
DOI: 10.1021/la1041019
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic FePt-Nanoparticles/Polycation Hybrid Capsules Designed for a Magnetically Guided Drug Delivery System

Abstract: The present Article describes the synthesis of ferromagnetic capsules approximately 330 nm in diameter with a nanometer-thick shell to apply to magnetic carriers in a magnetically guided drug delivery system. The magnetic shell of 5 nm in thickness is a nanohybrid, composed of ordered alloy FePt nanoparticles of approximately 3-4 nm in size and a polymer layer of a cationic polyelectrolyte, poly(diaryldimethylammonium chloride) (PDDA). The magnetic capsules have an excellent capacity for carrying medical drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 21 publications
(44 reference statements)
1
31
0
Order By: Relevance
“…1A–C). Our previous report demonstrated that FePt nanoparticles accumulate on organic compounds adsorbed on the surface of silica particles 18 confirming that the surface of the silica template particles treated with 1 or 5 wt% PDDA solution were not entirely covered with PDDA molecules, and that FePt nanoparticles accumulated only at the PDDA molecules adsorbed on the silica surface. This means that the FePt nanoparticles were selectively grown on the PDDA layer.…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…1A–C). Our previous report demonstrated that FePt nanoparticles accumulate on organic compounds adsorbed on the surface of silica particles 18 confirming that the surface of the silica template particles treated with 1 or 5 wt% PDDA solution were not entirely covered with PDDA molecules, and that FePt nanoparticles accumulated only at the PDDA molecules adsorbed on the silica surface. This means that the FePt nanoparticles were selectively grown on the PDDA layer.…”
Section: Resultssupporting
confidence: 65%
“…Our previous papers demonstrated two types of FePt magnetic capsules with thinner shells (d = 5–10 nm) compared with previously reported magnetic capsules 1 - 13 , 18 - 20 Scheme 1. shows the fabrication process for these two types of FePt magnetic capsules and representative transmission electron microscopy (TEM) images.…”
Section: Introductionmentioning
confidence: 51%
See 2 more Smart Citations
“…The possibility to synthesize molecules with desired structure and functionality in conjunction with a sophisticated thin film deposition technology enables the production of electrically, optically, magnetically and biologically active components on a nanometer scale [5,6]. A thin film can be deposited on a solid substrate by various techniques such as thermal evaporation, sputtering, electro-deposition, molecular beam epitaxy, adsorption from solution, Langmuir-Blodgett (LB) technique, and self-assembly.…”
Section: Introductionmentioning
confidence: 99%